Distingsi Epistemologis Tafsir al-‘Ilmi dan Tafsir bi al-‘Ilmi: Upaya Integratif Al-Qur’an dan Sains - Khairul Hafiz; Faqih Bramasta (Al Karima : Jurnal Studi Ilmu Al Quran dan Tafsir, 2026)
The integration of religion and science is often positioned as oppositional, even though the Qur'an contains verses that encourage scientific reflection. This research covers three main issues: the historicity of the emergence of tafsir al-'ilmi, the typology of the integration of the Qur'an and science, and the implementation of tafsir al-'ilmi and tafsir bi al-'ilmi in bridging revelation and science. This research uses a qualitative-descriptive approach with a literature study method, through a critical review of classical and contemporary literature. The results of the study show that tafsir al-'ilmi is explorative, trying to explore the scientific dimensions of the Qur'anic text, while tafsir bi al-'ilmi is more applicative by using scientific theory as a tool for interpretation. The typology of integration found shows a spectrum of approaches from affirmative to critical of modern science. These two models open up space for Qur'anic interpretation that is relevant to the development of science, while maintaining the integrity of its spiritual and theological values. This research recommends an interdisciplinary collaborative interpretation approach as a strategic step in strengthening epistemological integration between the Qur'an and science.